Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/eci.13432
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors of co‐existent pulmonary tuberculosis and lung cancer: A case‐control study

Abstract: Background Although the incidence of co‐existent pulmonary tuberculosis (PTB) and lung cancer in China is increasing, risk factors related to its development are still poorly understood. We aimed to investigate which clinical factors were associated with the odds of co‐existent PTB and lung cancer (PTB‐lung cancer) cases in a case‐control study. Method A total of 125 PTB‐lung cancer patients were enrolled by Beijing Chest Hospital as the case group between January 2012 and December 2016. Age‐ and sex‐matched P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…There have been rare reports on the coexistence of lung cancer and pulmonary TB in the same lesion, 1–3 while more cases occur in the same or different lobes. 5 , 6 Ashizawa et al reported a patient with a mass in the left lower lobe undergoing the left lower lobectomy. The specimen showed coexistence of adenocarcinoma and tuberculous granuloma.…”
Section: Discussionmentioning
confidence: 99%
“…There have been rare reports on the coexistence of lung cancer and pulmonary TB in the same lesion, 1–3 while more cases occur in the same or different lobes. 5 , 6 Ashizawa et al reported a patient with a mass in the left lower lobe undergoing the left lower lobectomy. The specimen showed coexistence of adenocarcinoma and tuberculous granuloma.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the good response to systemic chemotherapy in LC patients, the emergence of isolated sites or new foci, especially in typical anatomical sites of TB infection (e.g., upper lobes or apical lower lobes of the lung), should draw attention to the possibility of complicating a TB infection [104]. A previous retrospective study comparing LC patients with and without TB found that LC patients with TB were more likely to have symptoms such as cough, hemoptysis, nocturnal sweating, and more diverse CT findings such as lobar signs of mass, calcified lesions, pleural thickening, and hemorrhagic pleural effusion [105,106]. If these findings are present in LC patients, the possibility of developing TB complications should be considered.…”
Section: Diagnosis Of Tb Complicated By Lc Patientsmentioning
confidence: 99%
“…Epidemiological studies have revealed that TB is associated with an increased risk of lung cancer [ 6 , 7 ], or the survival and mortality of lung cancer [ 8 10 ], especially adenocarcinoma [ 11 ]. Cabrera-Sanchez J et al have demonstrated that patients diagnosed with TB are at an elevated risk of developing lung cancer [ 6 , 12 ].…”
Section: Introductionmentioning
confidence: 99%